Analisis Aktivitas Komunikasi Internal: Studi Kasus Pada Bagian Protokol dan Komunikasi Pimpinan Kota Bogor - Ulfa Alfiana; Oktavia Permatasari (Jurnal Penelitian Sosial Ilmu Komunikasi, 2025)
Organizational communication plays a strategic role in ensuring coordination effectiveness and managerial control within public sector institutions. This study aims to analyze the implementation of internal organizational communication in the Protocol and Leadership Communication Section (Prokompim) of the Bogor City Regional Secretariat. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observation, and documentation analysis. The findings reveal that internal communication activities in Prokompim take place through formal and informal channels, supported by various communication flows, including downward and upward vertical communication, horizontal communication, and diagonal or cross-unit communication. However, several communication barriers were identified, such as information filtering, selective perception, emotional factors, and inconsistent language usage, which affect communication accuracy and speed. From a theoretical perspective, these barriers reflect the presence of noise and semantic barriers within a bureaucratic communication structure. This study also highlights the importance of a supportive communication climate and rich communication media in minimizing misunderstandings and improving responsiveness. The findings contribute to the development of more effective internal communication strategies in local government organizations.